Violência no sertão : prática natural ou atentado às regras e às leis do norte de Minas e em Montes Claros entre 1830 e 1930 - Maria de Fátima Gomes Lima do Nascimento (2013)
The north of Minas and Montes Claros were described by chronicles, memoirs and reports of some travelers as a place of barbarism,uncivilization and criminals in the nineteenth and twentieth centuries (1830-1930). The reported violence incited a broader and morecritical analysis of this literature and the search for other sources (criminal processes) that could justify it or deny it. With this aim thisthesis examines whether the violence in the north of Minas Gerais hinterland was a natural practice or a violation of the rules and lawsof society in this space during the above mentioned period. Through political history and its interface with culture, it is verified that in the hinterland men used violence as a resource to access, exercise and permanence in power. A political culture was developed in thenorth of Minas and in Montes Claros where violence was an integral and strong part of the register of interpersonal, collective and institutional actions and where especially political issues were solved with shotguns. The hinterland became a social construction in the imagination, a land "where there was no law or order," and place of ambushes, stakeouts, indians, where the inlander "used to kill to see the fall", that is, despicable. However, during the studied period (1830-1930) the documentation can be seen otherwise. In thisalternative reading, we could see that interpersonal violence and the political practice in the North of Minas Gerais hinterland was a result of both the culture and the desire for political, economic and social power. In this perspective, we can understand the violence in the north of MinasGerais and in particular Montes Claros with a natural component of the history, political culture, memory and thehinterland itself.